Epidemiology, comorbidities at diagnosis and outcomes associated with HIV late diagnosis from 2010 to 2019 in a Belgian reference centre: A retrospective study. Issue 11 (10th November 2022) - Severin, Simon; Delforge, Marc; De Wit, Stéphane
Abstract: Objectives: Our objective was to investigate the demographic factors, comorbidities, and outcomes of patients with a late diagnosis (LD) of HIV in a Belgian HIV reference centre. Methods: All patients with HIV who presented for care between 2010 and 2019 were included. They were excluded if time between diagnosis and presentation or first CD4 count exceeded 6 months or if they had previously received antiretroviral therapy (ART). LD was defined as a CD4 cell count ≤350/mm 3 or an AIDS‐defining event at diagnosis. Data were retrospectively collected and included data on demographic variables, cardiovascular risk factors, comorbidities at diagnosis, first prescribed ART, and outcomes. Logistic regression was used to determine factors associated with LD. Results: Of 1078 patients, 427 (39.6%) were LD. In multivariable analysis, the following factors were associated with LD: non‐homosexual transmission route, being born in Sub‐Saharan Africa (SSA), and age ≥35 years. Prevalence at diagnosis of malignancies, diabetes, and cardiovascular diseases did not differ between non‐LD and LD, whereas renal impairment was more frequent in LD. In univariable analysis, high‐density lipoprotein (HDL) cholesterol <40 mg/dL and estimated glomerular filtration rate <60 ml/min were associated with LD; in multivariable analysis, only HDL cholesterol <40 mg/dL was associated. Patients with LD experienced more adverse events leading to a switch in ART, virological failure, and death during follow‐up. Conclusion: LD remains common in our centre, especially in non‐homosexual patients and those born in SSA. Although not associated with an important burden of comorbidities at diagnosis, it still results in poorer outcomes, emphasizing the need to expand coverage and access to HIV testing.